2023
DOI: 10.3390/s23031298
|View full text |Cite
|
Sign up to set email alerts
|

Smart Shoe Insole Based on Polydimethylsiloxane Composite Capacitive Sensors

Abstract: Nowadays, the study of the gait by analyzing the distribution of plantar pressure is a well-established technique. The use of intelligent insoles allows real-time monitoring of the user. Thus, collecting and analyzing information is a more accurate process than consultations in so-called gait laboratories. Most of the previous published studies consider the composition and operation of these insoles based on resistive sensors. However, the use of capacitive sensors could provide better results, in terms of lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…This review identified several types of technology integrated into the proposed measurement systems, including resistive technology [ 44 , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] ], piezoelectric [ 39 , 40 , 46 ], capacitive [ 41 , 52 , 66 ], inductive [ 49 , 51 ], fiber optics [ 38 , 50 , [67] , [68] , [69] , [70] , [71] , [72] ] and textile technology with piezoresistive features [ [73] , [74] , [75] ]. In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This review identified several types of technology integrated into the proposed measurement systems, including resistive technology [ 44 , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] ], piezoelectric [ 39 , 40 , 46 ], capacitive [ 41 , 52 , 66 ], inductive [ 49 , 51 ], fiber optics [ 38 , 50 , [67] , [68] , [69] , [70] , [71] , [72] ] and textile technology with piezoresistive features [ [73] , [74] , [75] ]. In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The advent of intelligent devices has stimulated efforts to improve the quality of life and, in particular, to the rapid development of wearable electronic devices. , Flexible wearable sensors with excellent portability and ergonomics have attracted considerable attention as medical monitoring devices, , intelligent robots, and wearable sensors. , Sensors based on the capacitive principle offer the advantages of easy setup, high intrinsic frequency, reduced hysteresis, and high pressure sensitivity compared with resistive and piezoelectric sensors . However, conventional dielectric layer materials for capacitive sensors are often made of silicone materials , and synthetic polymers, , which are problematic in terms of fit and biosafety . Hydrogel-based materials have emerged as a preferred choice due to their simple preparation, high accuracy, fast response, good repeatability, and wearability.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Sensors based on the capacitive principle offer the advantages of easy setup, high intrinsic frequency, reduced hysteresis, and high pressure sensitivity compared with resistive and piezoelectric sensors. 8 However, conventional dielectric layer materials for capacitive sensors are often made of silicone materials 9,10 and synthetic polymers, 11,12 which are problematic in terms of fit and biosafety. 13 Hydrogel-based materials have emerged as a preferred choice due to their simple preparation, high accuracy, fast response, good repeatability, and wearability.…”
Section: Introductionmentioning
confidence: 99%
“…Input devices collect data from the environment. They may measure temperature [ 46 ], medical parameters [ 47 ], displacement [ 48 ], pH [ 49 ], pressure [ 50 ], humidity [ 51 ], inertia [ 52 ], etc. Output devices broadcast messages to the external world.…”
Section: Introductionmentioning
confidence: 99%